Sustainable Entrepreneurship in the Light Engineering Industries: A Developing Country Perspective (Journal of Nepalese Business Studies, 2021)
The study strives to generate deep insights into sustainable entrepreneurship of the Light Engineering Industries (LEIs) from a developing country perspective. This exploratory research has conducted interview schedules with a total of 450 respondents (entrepreneurs 100, workers 350) from 100 LEIs scattered in different parts of Bangladesh. The LEIs belong to the green category as indicated by the environmental regulation of Bangladesh; however, the study has found a clear lack of environmental concerns to its day-to-day practices. Deficiencies are also observed in its value chain processes. This sector is lagging to take environmental initiatives for marketing their products and creating environmental and social risk awareness among workers. In addition to these, the study has found significant deficiencies in the workers' job satisfaction, job involvement, and organizational commitment factors that are hindering organizational effectiveness. For the current entrepreneurial activities to be sustainable, this sector needs to scrutinize its product, market, value chain, industry clusters, employee motivation and environmental concerns to its day-to-day operations.